1990
DOI: 10.1073/pnas.87.22.8855
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of hormone secretion on activation-inactivation kinetics of voltage-sensitive Ca2+ channels in pituitary gonadotrophs.

Abstract: The relationships between the activation status of voltage-sensitive Ca2+ channels and secretory responses were analyzed in perifused rat gonadotrophs during stimulation by high extraceflular K+ concentration ([K+] entry by at least two pathways, the best-defined of which is through VSCCs that are modulated by dihydropyridine agonist and antagonist analogs (1,3,9). The residual, dihydropyridine-insensitive entry ofCa2+ may occur through another type of VSCC or through receptor-operated Ca2" channels.To further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…SA). Such a profile of Ca2+ response to depolarization by high K+ is consistent with the presence of L-type VSCCs and with changes in their activationinactivation kinetics to produce the biphasic type of response (15). In agreement with this mechanism, addition of nifedipine ( (Fig.…”
Section: Effects Of Ca2+ Channel Regulators On [Ca2+1 and Gnrhsupporting
confidence: 80%
See 1 more Smart Citation
“…SA). Such a profile of Ca2+ response to depolarization by high K+ is consistent with the presence of L-type VSCCs and with changes in their activationinactivation kinetics to produce the biphasic type of response (15). In agreement with this mechanism, addition of nifedipine ( (Fig.…”
Section: Effects Of Ca2+ Channel Regulators On [Ca2+1 and Gnrhsupporting
confidence: 80%
“…First, activation of VSCCs by high K+-induced depolarization (15) in cultured hypothalamic neurons and GT1-1 neuronal cells leads to increased GnRH release, as in perifused hypothalamic explants (32,33 …”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have revealed that the kinetics of activation and inactivation of VGCCs underlines such a profile of [Ca 2ϩ ] i (Stojilkovic et al, 1990a). The addition of ET-1 during the sustained depolarization of cells induced a spike [Ca 2ϩ ] i response, but not inhibition of VGCI (Fig.…”
Section: Uncoupling Of Camentioning
confidence: 99%
“…This can arise from estrogen modulation of synaptic inputs and/or intrinsic conductances that govern the excitability of GnRH neurons and hence the pulsatile release of the peptide (Leranth et al, 1985;Kalra, 1993;Herbison, 1998). Synchronized pulsatile activity may be intrinsic to GnRH neurons, because GT1-7 cells generate pulses of GnRH in the absence of exogenous input (Stojilkovic et al, 1990; Martínez de la Escalera et al, 1992;Wetsel et al, 1992). Also, acutely dissociated EGFP-GnRH neurons fire episodically in a relatively autonomous manner (Kuehl-Kovarik et al, 2002.…”
Section: Introductionmentioning
confidence: 99%